Ressourcement after Vatican II essays in honor of Joseph Fessio, S.J. - Levering, Matthew 1971-; Healy, Nicholas J. (Ignatius Press, 2019)
"Beginning with a personal recollection of the achievements of Father Joseph Fessio, S.J., this work includes twelve essays by theologians who acknowledge a dept to Father Fessio and Ignatius Press. The writers treat a variety of topics including the Church, the liturgy, the interpretation of Scripture, and the development of doctrine, representing the interests of Father Fessio and the books that he published. The essays touch upon the major twentieth-century figures who influenced Father Fessio, such as Hans Urs von Balthasar, Louis Bouyer, Henri de Lubac, Joseph Ratzinger, and Josef Pieper. From its founding by Father Fessio in 1978, Ignatius Press has translated and printed works by these great thinkers and writers in order to make their contributions to the Church available to English-speaking Catholics."
Keywords: Fessio, Joseph -- 1941-; Katholische Theologie; Catholic Church; Vatican Council / (2nd / 1962-1965 / Basilica di San Pietro in Vaticano); Bible / Criticism and interpretation; Liturgics; Vatican Council; Bible; Criticism, interpretation, etc; Festschrift